Film paste and its preparation thereof - Hamidon, Mohd Nizar; Shahrokh Abadi, Mohammad Hadi Nezhad; Wagiran, Rahman; Shaari, Abdul Halim; Abdullah, Norhafizah (2011)
The present invention relates to an organic thick film paste which includes organic binder and active powder which provides conductive, semiconductive, resistive or insulative properties of the film paste. The thick film paste further includes glass powder. The organic binder is based-on linseed stand oil. The organic binder is mixed with finely ground active powder to form a conductive, semiconductive, resistive or insulative paste. The film paste is used to print a pattern or meander in form of thick–film structure on alumina, aluminum nitrate, ceramic or polymer substrates. The present invention also includes method of producing the organic thick film paste and also a method of producing organic thick film paste printed on alumina, aluminum nitrate or polymer substrates.